Dental and maxillofacial outcomes in childhood head and neck cancer survivors: a retrospective study and dental care considerations - Sampaio Nobrega, Kaio Heide; Schulz, Riéli Elis; Alves, Fabio Abreu; Lima da Costa, Cecilia Maria; Araujo, Juliane Piragine (Journal of Oral Diagnosis, 2024)
Cancer treatment during childhood, including head and neck radiotherapy and chemotherapy, can cause persistent dental and maxillofacial changes, which may lead to long-term complications in dental care and oral rehabilitation. Objective: The aim of this study was to evaluate dental and maxillofacial alterations resulting from childhood head and neck cancer treatment and discuss considerations regarding dental care for these patients. Methods: This retrospective study utilized a Cancer Center database, including patients referred to the Stomatology Department from 2004 to 2018. Results: The sample comprised 12 patients (7 males and 5 females) with a mean age of 5 years at diagnosis, who underwent oncological treatment in the head and neck region. Half exhibited facial bone hypoplasia, predominantly mandibular (33.33%) over maxillary (16.67%). Nearly all patients showed dental abnormalities, including agenesis (50%), supernumerary teeth (16.67%), and root formation anomalies (66%). Conclusion: This study underscores the importance of understanding these treatment-related alterations to ensure appropriate dental care for these patients. The involvement of a dental surgeon is crucial to providing comprehensive care and effectively monitoring any dental and maxillofacial complications.